2009
DOI: 10.1159/000244512
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller-Dor Surgery for Esophageal Achalasia: Impact of Intraoperative Real-Time Manometric Feedback on Postoperative Outcomes

Abstract: Background: Laparoscopic Heller myotomy with Dor fundoplication (LHD) is one of the most established surgical procedures for esophageal achalasia. Preoperative esophageal manometry has been reported as useful to evaluate lower esophageal sphincter (LES) pressure. However, the feasibility, safety, and impact of its intraoperative use have not been fully evaluated, especially when enhanced with real-time 3-D pressure imaging. Methods: LHD was attempted on 24 consecutive patients with esophageal achalasia. Manome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Any residual fibers can be divided as needed. Some authors have suggested the use of intraoperative manometry to assess the myotomy for completeness [43], but comparative data are lacking. The myotomy also can be assessed for perforation by placing it under a column of saline and inflating gently through the endoscope.…”
Section: Brief Description Of Myotomy Techniquementioning
confidence: 99%
“…Any residual fibers can be divided as needed. Some authors have suggested the use of intraoperative manometry to assess the myotomy for completeness [43], but comparative data are lacking. The myotomy also can be assessed for perforation by placing it under a column of saline and inflating gently through the endoscope.…”
Section: Brief Description Of Myotomy Techniquementioning
confidence: 99%
“…13 Current practice is to perform a myotomy that adheres to whatever length the surgeon believes is appropriate based on the above, and to determine the adequacy of the myotomy based on the appearance of the EGJ endoscopically following myotomy. 3 Some investigators advocate for the use of intraoperative manometry, 14,15 but this is cumbersome and not a common practice. An intraoperative, objective assessment that could guide the surgeon and provide real-time feedback that the extent of the myotomy is adequate would be invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Although advanced age is frequently viewed as an obstacle to surgery, mostly because of the increased frequency of clinically significant comorbidi ties, a 2010 study suggests that laparoscopic myotomy can achieve excellent outcomes in patients >60 years of age. 62 The introduction of realtime, intra operative mano metry 63,64 and robotic-assisted myotomy 65,66 may further improve postoperative outcomes, but these methods are not widely established.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…At our center, to avoid misinterpretation of success by immediate treatment effects, such as intramural hematoma, we preferentially perform these studies 4 weeks after therapy. However, some centers assess treatment success by esophageal manometry intraoperatively 63,64 or immediately after pneumatic dilation. 12 In a very ambitious approach, Hulselmans et al 12 even performed serial pneumatic dilations with daily esophageal manometry over 1-3 days to achieve and assess their manometric treatment goal.…”
Section: Surveillancementioning
confidence: 99%